2020
DOI: 10.1371/journal.pone.0236433
|View full text |Cite
|
Sign up to set email alerts
|

Coptidis alkaloids extracted from Coptis chinensis Franch attenuate IFN-γ-induced destruction of bone marrow cells

Abstract: Coptidis alkaloids are the primary active components of Coptis chinensis Franch. Clinical and pharmacodynamic studies have confirmed that Coptidis alkaloids have multiple therapeutic effects including anti-inflammatory, antioxidant and antitumor effects, and they are usually used to treat various inflammatory disorders and related diseases. Mouse bone marrow cells (BMCs) were isolated from BALB/c mice. Immune-mediated destruction of BMCs was induced by interferon (IFN)-γ. High-performance liquid chromatography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…With the integration of traditional and modern medicine, an increasing number of studies have found that traditional Chinese monomers have the dual advantages of traditional Chinese medicine and chemical medicine ( 205 ), which can optimise their functions. Therefore, to maximise the curative effect, adequacy of theory, and achieve better integration of traditional Chinese and Western medicines, we will pay more attention to the treatments of diseases using traditional Chinese medicine monomers should be further investigated ( 206 ).…”
Section: Immunotherapy For Rheumatoid Arthritis and Postmenopausal Os...mentioning
confidence: 99%
“…With the integration of traditional and modern medicine, an increasing number of studies have found that traditional Chinese monomers have the dual advantages of traditional Chinese medicine and chemical medicine ( 205 ), which can optimise their functions. Therefore, to maximise the curative effect, adequacy of theory, and achieve better integration of traditional Chinese and Western medicines, we will pay more attention to the treatments of diseases using traditional Chinese medicine monomers should be further investigated ( 206 ).…”
Section: Immunotherapy For Rheumatoid Arthritis and Postmenopausal Os...mentioning
confidence: 99%
“…In the psoriasis model, further studies are needed to determine whether coptisine suppresses the proportion of Th1 and Th17 cells and regulates associated transcription factors. Coptidis alkaloids, which are present in the aqueous extract of Coptidis Rhizoma, have been demonstrated to inhibit the proliferation of Th1/Th17 and regulatory T (Treg) cells in mouse bone marrow cells by suppressing T-bet (the transcription factor of Th1) and Foxp3 (the transcription factor of Treg) [74]. Furthermore, it has been revealed that herbal formulas containing coptisine also affect Th cell-specific transcription factors such as T-bet and RORγt (the transcription factor of Th17) [75].…”
Section: Limitationmentioning
confidence: 99%